2015
DOI: 10.1080/15421406.2015.1026750
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dot Doped Ferroelectric Liquid Crystal System: Investigation of Electro-Optical Parameters and Relaxation Behavior

Abstract: The effect of QDs on the dielectric and electro-optical (E-O) properties of different ferroelectric liquid crystal matrices has been studied in the SmC * phase. A substantial change in the different parameters like tilt angle, spontaneous polarization and relative permittivity has been observed for the doped system. For the better understanding of the effect of QDs on FLC relaxation process another quantum dot CdSe has been dispersed in two other FLC systems 16/100 and DOBAMBC. The effect of QDs on the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Reprinted from [63], with the permission of AIP Publishing. ultrasonication of the mixtures at temperatures, well above their isotropic transition temperature [38,39,[54][55][56][57][58][59][60][61][62][63].…”
Section: Preparation and Alignment Of Snms-flcs Nanocompositesmentioning
confidence: 99%
See 3 more Smart Citations
“…Reprinted from [63], with the permission of AIP Publishing. ultrasonication of the mixtures at temperatures, well above their isotropic transition temperature [38,39,[54][55][56][57][58][59][60][61][62][63].…”
Section: Preparation and Alignment Of Snms-flcs Nanocompositesmentioning
confidence: 99%
“…The impact of SNMs on phase transition temperatures of FLCs can also be probed through dielectric spectroscopy. Under this framework, Gupta et al [59] investigated the impact of two different semiconducting QDs i.e., Cd 1−x Zn x S/ZnS (QD1, ∼8.7 nm) and CdSe (QD2, ∼3.5 nm) on dielectric features of three distinct FLCs (Felix 17/000, Felix 16/00 and DOBAMBC). The mixing of QD1 was done with FLC (Felix 17/000).…”
Section: Dielectric Studies Of Snms-flcs Nanocompositesmentioning
confidence: 99%
See 2 more Smart Citations
“…3.5 nm, 1.0 wt %), and it was found that the tilt angle was smaller by about 8° (as an attraction effect between quantum dots surrounding the molecules), and P s decreased (as the secondary order parameter coupling with the tilt angle) for the doped Felix 17/000. Moreover, a new relaxation process around 10 5 Hz was revealed for the doped Felix 16/100 [ 27 ]. Das et al, after addition of Au nanoparticles (ca.…”
Section: Introductionmentioning
confidence: 99%